2022
DOI: 10.7759/cureus.32018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drain Insertion After Appendicectomy for Complicated Appendicitis: A Systematic Review and Meta-Analysis

Abstract: This meta-analysis aims to evaluate the comparative outcomes of drain insertion versus no drain after appendicectomy for complicated appendicitis. A systematic search of PubMed, Cochrane Library and Scopus was conducted, and all studies comparing drain versus no drain after appendicectomy for complicated appendicitis were included. Abdominal collection, surgical site infection (SSI), bowel obstruction, faecal fistula, paralytic ileus, length of hospital stay (LOS) and mortality were the evaluated outcome param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Reasons may be that its use was not only associated with longer operative time but also with a rise in pain sensitivity following the use of remifentanil during surgery (Ren et al, 2023). Drainage tubes are routinely placed in most procedures to prevent fluid collection and timely find complications after surgery (Abu et al, 2022). This study found that drain is one of the predictors of pain during the early post-operative period.…”
Section: Surgical Related Factors: Consumption Of Intraoperative Remi...mentioning
confidence: 79%
“…Reasons may be that its use was not only associated with longer operative time but also with a rise in pain sensitivity following the use of remifentanil during surgery (Ren et al, 2023). Drainage tubes are routinely placed in most procedures to prevent fluid collection and timely find complications after surgery (Abu et al, 2022). This study found that drain is one of the predictors of pain during the early post-operative period.…”
Section: Surgical Related Factors: Consumption Of Intraoperative Remi...mentioning
confidence: 79%
“…This obstruction can result from the drain’s mechanical presence (foreign object) or through the potential introduction of extra-abdominal bacteria, and thus, infection and scarring [ 67 ]. Furthermore, Cheng et al observed that routine intra-abdominal drain placement after open emergency appendectomy for complicated appendicitis was not associated with reduced risk of intraperitoneal abscess formation [ 68 ]. In another systematic review and meta-analysis of 17 studies consisting of 4255 patients with complicated appendicitis, 1580 underwent abdominal drainage, while 2657 did not [ 69 ].…”
Section: Role Of Drain Placementmentioning
confidence: 99%
“…"A meta-analysis by Abu et al evaluated drain insertion after appendectomy for complicated appendicitis, and they concluded that drain insertion does not increase the risk of intraabdominal abscess formation, but it significantly increases the risk of surgical site infection, length of hospital stays and bowel obstruction" [43].…”
Section: Irrigation or Suction And Use Of Drains In Complicated Appen...mentioning
confidence: 99%